1969
DOI: 10.1139/v69-072
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of uridine 2′,3′-carbonates to anhydrouridines

Abstract: Uridine 2',3'-carbonates are readily converted t o 2,2'-anhydrouridines in hot diniethyl formamide with base catalysis. 3',5'-Di-0-trityluridine is converted to 3',5'-di-0-trityl-2,2'-anyhdro-1-a-D-arabinofuranosyluracil with diphenyl carbonate in the presence of sodium bicarbonate in hot dimethyl formamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
1988
1988

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…We had noted that a 2',3'-carbonate on a pyrimidine nucleoside is readily displaced by nucleophilic groups on the base ring (34). Further it has been found that there is no need to block either the 5'-hydroxyl or amine groups on the base ring in forming 2',3'-carbonates of purine nucleosides (16,35).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…We had noted that a 2',3'-carbonate on a pyrimidine nucleoside is readily displaced by nucleophilic groups on the base ring (34). Further it has been found that there is no need to block either the 5'-hydroxyl or amine groups on the base ring in forming 2',3'-carbonates of purine nucleosides (16,35).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Preparation of Glycosyl Azides.-The per-0-acetyl-/3-D-glycosyl azides la-d were prepared by heating the corresponding per-O-acetyl-a-D-glycosyl halides with sodium azide in dimethylformamide (DMF) by a procedure similar to that used by Yamamoto, et al,10 and Carrington, et al 11 The general procedure is described below.…”
Section: Methodsmentioning
confidence: 99%